The relationship between trauma symptoms and immediate and delayed suggestibility in children who have been sexually abused. Issue 3 (2nd August 2020) - Gudjonsson, Gisli; Vagni, Monia; Maiorano, Tiziana; Pajardi, Daniela
Abstract: There is general absence of research about the relationship between trauma symptoms and immediate and delayed suggestibility in children who have been sexually abused. The participants were 134 children aged between 7 and 17 years with a history of reported sexual abuse. All children completed the Gudjonsson Suggestibility Scale (2), a non‐verbal IQ test, and The University of California at Los Angeles Child/Adolescent Reaction Index for post‐traumatic stress (UCLA‐PTSD‐RI‐5). Delayed suggestibility was measured after a 1 week delay. A Hierarchical Regression showed that trauma symptoms accounted overall for 43.4% of the variance in delayed suggestibility after controlling for age, sex, IQ, and immediate recall (a large effect size). There was a small shared variance between trauma and immediate suggestibility (low effect size). The findings strongly suggest that the severity of trauma symptoms impact more on delayed than immediate suggestibility. The theoretical and forensic implications are discussed.